(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2024)
The inability of governments at various levels to consistently provide adequate water contributed to the proliferation of the water manufacture in Nigeria. The study will examine the rationale for and framework of NAFDAC and CPC, determine the effect of the two agencies on the supplies and consumption of sachet water in the states, and examine the challenges confronting NAFDAC and CPC in regulating the supplies and consumption of sachet water in Ekiti and Ondo States. The study will employ primary and secondary sources of data. The primary data will be sourced through questionnaire administer on sampled general public, In-Depth Interview (IDI) with principal officers of NAFDAC and CPC, sachet water manufacturers and civil society groups, Focus Group Discussions (FGDs) will be conducted among vulnerable rural dwellers. Secondary data are sourced from relevant text, internet sources, and official publications on NAFDAC and CPC. Tables, graphs, chi-square and content analytical methods will employed for data analysis.